Pengembangan Sistem Informasi Pengiriman Paket POS untuk Meningkatkan Efisiensi Layanan Kurir - Rizar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2022)
This research focuses on the development and implementation of a Package Delivery Information System for postal services to enhance courier service efficiency. The system is designed to streamline the management of package delivery processes, ensuring accurate tracking, timely updates, and efficient route planning. Key features of the system include real-time tracking of packages, automated notifications for customers, and optimized route management for couriers. By integrating GPS technology and advanced data analytics, the system provides a robust solution for managing large volumes of deliveries with high precision. The study outlines the design, development, and deployment phases of the system, highlighting the selection of appropriate technologies, system architecture, and user interface design. The implementation of this system is expected to lead to significant improvements in delivery times, customer satisfaction, and operational efficiency. The paper also discusses the challenges encountered during the development and deployment phases, as well as the strategies adopted to overcome these challenges. Results indicate that the Package Delivery Information System effectively addresses the limitations of traditional delivery management practices, offering a scalable and reliable solution for postal services aiming to enhance their courier operations.